Stability analysis for cane and sugar yield of advanced sugarcane (Saccharum officinarum) genotypes - KUMAR, DEVENDRA; MEENA, L R; MEENA, L K; SINGH, KHUSHYAL; SINGH, S P (The Indian Journal of Agricultural Sciences, 2023)
The present investigation was undertaken to ascertain stable genotypes across nine environments. Ten advanced genotypes including three checks of themid-late group were evaluated for their adaptability in respect of cane yield, CCS yield and sucrose (%) for two crop seasons 2009-10 and 2010-11 under three locations with three cuttings. The stability of genotypes was worked out by using the model of Eberhart and Russell (1966). The regression coefficient (bi) and deviation from regression (S2 di) were used to define genotypic stability. Mean square due to G x E for all the characters was not significant. The genotypes CoBln 05502, CoP 05437 and CoP 9301 were stable and suitable for cane and CCS yield under favorable environments, while BO 91 was stable for CCS yield and sucrose per cent in juice under unfavorable environmental conditions. Apart from this, genotype CoP 05437 was on top and most stable and widely adaptable in cane and CCS yield across nine environments.